Brahman Cross Carcass Production on Different Frame Size - Rafsanjani, Roviki Rafsanjani; Hary Nugroho; Trinil susilawati (Jurnal Agro Veteriner, 2023)
This study observed Brahman cross steer carcass production, (slaughter weight, carcass weight, and dressing percentage). The material used was 166 heads of white Brahman cross steer, with an average slaughter weight of 424.40–35.86 kg, and the range of age was 1.5–2 years. Sample of this study was Brahman cross steers with 83 heads large framed and 83 heads medium framed. The study method used was case studies. The obtained data was analyzed with independent t-tests, simple linear regression, and correlation. Results showed that frame size was highly significant (P<0.01) in slaughterweight. The average slaughterweight on the medium frame was 415.82 ± 35.98 kg, and the medium frame was 432.98 ± 33.83 kg. Frame size is also highly significant (P<0.05) in carcass weight. The correlation between slaughter weight and carcass weight was very close, with a correlation coefficient of 0.87 on medium frames and 0.90 on large frames. This study concluded that Brahman cross steers with large frames resulted in slaughter weight and carcass weight higher than medium frames but produced the same carcass percentage.